Morfologia e Sedimentologia da Plataforma Continental Interna entre as Praias Porto de Galinhas e Campos - Litoral Sul de Pernambuco, Brasil - VAZ MANSO, VALDIR DO AMARAL; CORRÊA, IRAN CARLOS STALLIVIERE; GUERRA, NÚBIA (Pesquisas em Geociências, 2003)
<!-- .p { text-align: justify; } --> The analysis of geomorphic and sedimentological characteristics of the inner continental shelf is an important propriety to studies of the coastal zone since they inform the conditions of the sea bottom, the predominant features and the types of associated sediments. Associated to morfodinamic study it can, for example, identify predisposed areas to erosive processes. The present paper shows the batimetry (to -20m) and the sediments distribution in the inner continental shelf between Porto de Galinhas and Campos beaches, south coast of Pernambuco State. The work results constitute pioneering mark in the inner continental shelf of the Pernambuco state.